UPAYA MENINGKATKAN MOTIVASI BELAJAR BAHASA INDONESIA DENGAN PENERAPAN METODE CERAMAH BERVARIASI SISWA KELAS III SDN I SIDOGIRI PASURUAN - Eminarni, Eminarni (Jurnal Likhitaprajna, 2019)
The application of varied lecture methods can arouse student learning motivation, because this method students can be active in providing responses to questions posed by teacher and students. Besides this method is also not boring students in teaching and learning activities, and the teacher can use a variety of media that is accompanied by fresh humor so that the classroom atmosphere becomes excited and the results achieved will be better. The purpose of this study is to determine whether there is an increase in students’ motivation by using varied lecture methods. This type of research is Classroom Action Research. Subjects were 47 students in State Elementary School I of Sidogiri. In this study conducted 2 cycles. The results showed that in the first cycle 32 students got grades according to graduation standards and 15 students did not meet graduation standards. However, in the second cycle showed that 42 students scored according to the graduation standard and only five said and only 5 students did not meet the graduation standard. Keywords: learning motivation. lecture method, varies